Рекламная деятельность медиорганизации в сети Интернет - Pak E. A. (Economics and management: problems, trends and future development, 2017)
In work are considered the latest formats and standards of advertizing activities of one of the largest company in the Internet market of Russia - Mail.ru Group
Keywords: Интернет; информация; internet; information; рекламная деятельность; сетевая экономика; информационно-сетевая среда; advertizing activities; network economy; information and network environment